2020
DOI: 10.1111/bcp.14547
|View full text |Cite
|
Sign up to set email alerts
|

Impact of enantiomer‐specific changes in pharmacokinetics between infants and adults on the target concentration of racemic ketorolac: A pooled analysis

Abstract: Ketorolac is a nonsteroidal anti-inflammatory racemic drug with analgesic effects only attributed to its S-enantiomer. The aim of this study is to quantify enantiomer-specific maturational pharmacokinetics (PK) of ketorolac and investigate if the contribution of both enantiomers to the total ketorolac concentration remains equal between infants and adults or if a change in target racemic concentration should be considered when applied to infants. Methods: Data were pooled from 5 different studies in adults, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…That enantiomers may have different kinetic profiles and may even be best described using different compartment models has been seen for other compounds such as S- and R-ketorolac. 23…”
Section: Discussionmentioning
confidence: 99%
“…That enantiomers may have different kinetic profiles and may even be best described using different compartment models has been seen for other compounds such as S- and R-ketorolac. 23…”
Section: Discussionmentioning
confidence: 99%
“…Overview of studies published after 2000 [ 17 , 25 28 , 33 , 34 , 38 , 39 , 41 , 42 , 46 , 51 , 52 , 63 , 64 , 67 , 71 , 72 , 273 , 274 , 277 – 280 , 317 , 318 ] No. of patients Age (range) Body weight [kg] Dose [mg/kg] Compartment absorption elimination PK parameters References F [%] AUC [mg⋅h/L] C max [mg/L] T max [h] t ½ [h] V d / F [L/kg] CL/ F [L/h] Metabolism Ibuprofen 9 4.2 ± 1.9 weeks (1–7 weeks) 4.4 ± 0.6 19.0 ± 1.6 RECT NA NA 299 ± 69 49.2 ± 20.7 1.9 ± 1.2 h 4.6 ± 5.1 NA NA CYP2C8 CYP2C9 UGT2B7 [ 278 ] 8 16.1 ± 6.9 weeks (8–25 weeks) 6.7 ± 1.4 …”
Section: Pharmacokinetics Of Non-steroidal Anti-inflammatory Drugs (N...mentioning
confidence: 99%
“…This dosing regimen is in agreement with current practice. Recently, it was shown that S-enantiomers produce different concentrations between infants and adults, and therefore requires further research as this difference in S-enantiomer concentration may have an important effect on analgesia since the S-enantiomer is solely responsible for the analgesic effect [ 51 ]. When clinical and patient covariates were assessed for effects on PK, it was found that no covariates were statistically significant when accounted for body size [ 52 ].…”
Section: Pharmacokinetics Of Non-steroidal Anti-inflammatory Drugs (N...mentioning
confidence: 99%
“…There is also a low risk of gastrointestinal and operative site bleeding and acute renal insufficiency. Some people also experience itching, diarrhea, sweating, self-limiting wheezing, edema and hyperkalemia (17) . Interestingly, the current study compared the first request analgesia and total analgesia between studied groups.…”
Section: ------------------------------------------------------------...mentioning
confidence: 99%